Speech Acts in Ariana Grande’s Song We Can’t Be Friends - Fadilatul Khotimah; Adip Arifin; Serdaniar Ita Dhamina; Ririn Ardita; Rita Ristiana (English Language Education Department, Universitas Majalengka, 2026)
This study analyzes speech acts types in Ariana Grande’s song We Can’t Be Friends. The song explores themes of heartbreak and personal growth, providing insight into emotional complexity. The descriptive qualitative method was employed in the study. The forms of speech acts are identified based on Searle’s theory, comprising of expressive, representative, directive, commissive, and declarative. The analysis identifies key speech acts in the lyrics: expressive acts (15 lines); representative acts (10 lines); directive acts (4 lines); and commissive acts (3 lines). Representative acts contextualize the emotional narrative, while directive acts guided the listener toward introspection. Expressive acts dominated the lyrics, conveying grief and self-reflection, while commissive and declarative acts emphasized the emotional transformation and desire for change. The findings demonstrated that the song used linguistic elements not only to explore personal emotions but also to foster emotional connections with the audience.